Implementation of data mining with the c4.5 algorithm for student majors (Case Study: SMA N 1 Bp.Mandoge) - Nabilah putri; M. Safii (Asosiasi Perguruan Tinggi Informatika dan Ilmu Komputer (APTIKOM) Provinsi Sumatera Utara, 2023)
Classification of student majors is the process of grouping students according to abilities (values), talents and interests that are relatively the same so that the lessons that will be given to students will be more focused and directed. The process of classifying student data can be explored for patterns in the field of data mining, namely the process of obtaining relationships or patterns from large data so as to provide useful indications. SMA N 1 Bp.Mandoge is one of the educational institutions that started introducing majors and divided them into two choices of majors, namely